The Judge’s Authority to Amend a Contract During the Formation Stage - Faisal Satouf Al-Assaf; Abdulrahman Abdullah Al-Mehdar (International Journal of Law Research and Studies, 2025)
This study dealt with the authority of the civil judge to amend the contract in the formation stage. It was divided into two sections, each of which has two requirements. The first section dealt with the judge’s intervention due to fraud, then the second section dealt with the judge’s intervention due to acquiescence The main objective of the study is to understand fraud and submission and their conditions so that the judge can amend contracts to avoid invalidation. We adopted the comparative approach to reach the objectives and results of the study The study concluded that mere fraud is not sufficient to activate the judge’s power of amendment. Rather, it requires the presence of conditions for fraud, including that this fraud be gross and not minor. We distinguished between fraud and exploitation and the standards used in that, and the judiciary’s standards in assessing fraud were explained. Then we defined the contract of adhesion, its characteristics and legal nature, and we mentioned the conditions for the judge’s intervention in contracts of adhesion and their forms.